2018
DOI: 10.1057/s41287-018-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Relative Success of Collaborative Forestry Research Projects in Indonesia

Abstract: The success of research for development projects is of keen interest to project funders and participating researchers, and underpins project impact. This paper reports a qualitative investigation of factors identified by project researchers as affecting relative success in ten collaborative forestry research projects in Indonesia. Interviews with 33 project participants identified 30 factors that influence project success. The most frequently identified factors were scientists' commitment and collaboration; co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Existing structures of how research is designed and funded, how research teams work to complete objectives and what is considered successful outputs and outcomes need to be reshaped in integrated research. Bartlett (2018) outlines eight criteria for success in international programmes of work. We outline these in Table 5 and show how, from our experience, integrated research can be explicitly considered.…”
Section: Reflections On Conducting Participatory and Integrated Researchmentioning
confidence: 99%
“…Existing structures of how research is designed and funded, how research teams work to complete objectives and what is considered successful outputs and outcomes need to be reshaped in integrated research. Bartlett (2018) outlines eight criteria for success in international programmes of work. We outline these in Table 5 and show how, from our experience, integrated research can be explicitly considered.…”
Section: Reflections On Conducting Participatory and Integrated Researchmentioning
confidence: 99%
“…This methodology has been applied in three case studies of ACIAR forestry projects, covering ten projects from Vietnam, reported by Bartlett et al (2017), ten projects from Indonesia, reported by Bartlett (2018a), and ten projects from Papua New Guinea, reported by Bartlett (2018b). About one quarter of the 30 forestry projects (seven) were evaluated as having high achievements and high impacts, with three of these implemented in Vietnam and four in Indonesia.…”
Section: Striving For Success In International Forestry Researchmentioning
confidence: 99%